1999
DOI: 10.1016/s0741-5214(99)70054-6
|View full text |Cite
|
Sign up to set email alerts
|

Dermal tissue fibrosis in patients with chronic venous insufficiency is associated with increased transforming growth factor-β1 gene expression and protein production

Abstract: Our study indicated that activated leukocytes traverse perivascular cuffs and release active TGF-beta(1). Positive TGF-beta(1) staining results of dermal fibroblasts were observed and suggest that fibroblasts are the targets of activated interstitial leukocytes. Increased protein production, despite normal levels of gene transcripts in patients in classes 5 and 6, suggests that alternate mechanisms other than gene transcription regulate protein production. A potential mechanism for quick access and release is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 21 publications
(36 reference statements)
3
67
0
3
Order By: Relevance
“…To test the hypothesis that elevated pressure produces premature senescence in dermal fibroblasts, we have developed an in vitro model using a special pressurized incubator [9] and a methodology to specifically test for cellular senescence. In addition, because TGF-␤ has been implicated as a possible mediator of inflammation and delayed healing of venous ulcers [10,11], we examined the effects of both pressure and TGF-␤ on cellular senescence, hypothesizing that TGF-␤ would accelerate the aging phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…To test the hypothesis that elevated pressure produces premature senescence in dermal fibroblasts, we have developed an in vitro model using a special pressurized incubator [9] and a methodology to specifically test for cellular senescence. In addition, because TGF-␤ has been implicated as a possible mediator of inflammation and delayed healing of venous ulcers [10,11], we examined the effects of both pressure and TGF-␤ on cellular senescence, hypothesizing that TGF-␤ would accelerate the aging phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…1002/eji.200425147] suggested that there may be a link between increased mast cell density and endomyocardial fibrosis. Recent reports have demonstrated a definite role of mast cells in other fibrogenic disorders [19][20][21]. Paolocci et al [22] showed that the degranulation of mast cells and eosinophils might induce myocardial damage and dysfunction in rats challenged with Trichinella spiralis.…”
Section: Introductionmentioning
confidence: 99%
“…52,57,58 In BM fibrosis, activated monocytes are one of the cellular sources of TGF-␤. 6 Preliminary evidence indicated that the monocytes could be a source of the increased SP in the BM and circulation (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%